#243 : Comparison of IVF Outcome Following Follitropin Alfa and Follitropin Delta Utilization at Melati Clinic, Harapan Kita Women and Children Hospital - Agus Supriyadi; Novita Prasetiawati; Hadi Sjarbaini; Sudirmanto Tarigan; Gde Suardana; Mohammad Haekal; Deana Rosaria Indah; Gangsar Pariyanti (Fertility & Reproduction, 2023)
Background and Aims: Follitropin delta is the third recombinant FSH (rFSH) preparation developed with an individualized dosing regimen based on patient’s body weight and AMH level. According to the existing report, a daily dose of follitropin delta provides an equivalent ovarian response to that of follitropin alfa. However, the effect of follitropin delta on the resulting embryo and biochemical pregnancy remains to be elucidated. Hence, the present study aims to evaluate the effect of follitropin delta on embryo quality and biochemical pregnancy rates compared with that of follitropin alfa in an in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycle. Methods: A retrospective cohort study was conducted between January and December 2022 at Melati Clinic, Harapan Kita Women and Children Hospital. A total of 59 IVF/ICSI cycles stimulated with follitropin alfa and 26 IVF/ICSI cycles treated with follitropin delta were subsequently analyzed. Results: After analysis, no significant difference was observed regarding the embryo quality of both treatments (P>0.05). The median of the good, moderate, and poor embryos in the follitropin alfa and follitropin delta group was 2 vs. 3, 1 vs. 2, and 2 vs. 2, respectively. Similarly, the biochemical pregnancy rate between the follitropin alfa and follitropin delta group was comparable (25% vs. 15%, P>0.05). Conclusions: In conclusion, our study suggests that stimulation with follitropin delta in IVF/ICSI cycles yields a similar embryo quality and biochemical pregnancy rates to those of follitropin alfa.